Cervical Cancer Screening On 1000 Healthy Asymptomatic Women Residing In Slum of Rajshahi City of Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Cervical carcinoma is an important cause of mortality among adult women.Objective: The purpose of the present study was to detect the pre-cancerous condition of cervix in women.Methodology: This cross sectional study was carried out in the OPD of a tertiary care hospital of Rajshahi City in Bangladesh during the year June 2010 to August 2011. Healthy asymptomatic women residing in slum of Rajshahi city with a marital age of 8 years and above were included as study population. VIA test was performed in all women. The VIA positive cases were invited for colposcopy and directed biopsies were obtained from women who were colposcopically positive.Result: A total number of 1000 women were studied. Among them 80(8%) women were VIA positive. These positive cases were also referred for colposcopy. Out of the 80 cases, 26 (32%) were colposcopically normal and 50(63%) were CIN-1 and 4(5%) women were CIN II. Directed biopsy was done among colposcopically positive group. Histopathological examination shows 44 (82%) were CIN-1 and 4(7%) were CIN- II and 6(11%) were chronic cervicities.Conclusion: Cervical screening of the slum area women shows an important number of women suffering from precancerous condition of which CIN-l is the most common.J Shaheed Suhrawardy Med Coll, 2015; 7(1):14-17